Induced plant volatiles allow sensitive monitoring of plant health status in greenhouses - Jansen, Roel MC (Landes Bioscience, 2009)
A novel approach to support the inspection of greenhouse crops is based on the measurement of volatile organic compounds emitted by unhealthy plants.This approach has attracted some serious interest over the last decade. In pursuit of this interest, we performed several experiments at the laboratory-scale to pinpoint marker volatiles that can be used to indicate certain health problems. In addition to these laboratory experiments, pilot and model studies were performed in order to verify the validity of these marker volatiles under real-world conditions. This paper provides an overview of results and gives an outlook on the use of plant volatiles for plant health monitoring.